maths

HideShow resource information

Expanding double brackets

Expanding double brackets

(x + 4)(x + 3)=

 

 

(x + 6)(x – 4)=

 

 

(2x + 7)(3x + 4)=

 

 

(x - 2)(x - 6)=

1 of 2

maths

Expanding brackets

(x - 2)(x - 6)=

 

(x + 4)(x + 3)=

 

(x + 6)(x – 4)=

 

(2x + 7)(3x + 4)=

2 of 2

Comments

? Secret - Team GR

perhaps  give the answers in the last few cards so people can check they have done it correctly

Similar Mathematics resources:

See all Mathematics resources »See all resources »